Bad Credit, No Problem? Credit and Labor Market Consequences of Bad Credit Reports - DOBBIE, WILL; GOLDSMITH‐PINKHAM, PAUL; MAHONEY, NEALE; SONG, JAE (Journal of Finance, 2020)
ABSTRACT We study the financial and labor market impacts of bad credit reports. Using difference‐in‐differences variation from the staggered removal of bankruptcy flags, we show that bankruptcy flag removal leads to economically large increases in credit limits and borrowing. Using administrative tax records linked to personal bankruptcy records, we estimate economically small effects of flag removal on employment and earnings outcomes. We rationalize these contrasting results by showing that, conditional on basic observables, “hidden” bankruptcy flags are strongly correlated with adverse credit market outcomes but have no predictive power for measures of job performance.